Hydrogeomorphometry of the Cutia river microbasin, South-Western Amazon, Brazil (Research, Society and Development, 2021)
Planning for the management of natural resources is essential for sustainable development in the Amazon region and is based on information associated with landscape characteristics. Given the above, the present study aims to provide geometric, topographic, and hydrographic information on the Cutia river microbasin, which belongs to the Guaporé river basin, an important basin in the state of Rondônia. This information was obtained through equations available in the literature and remote sensing, using the softwares: QGIS 2.10.1, TrackMaker and Google Earth, and altimetric images from the ALOS satellite (Sensor Palsar). The microbasin has an area of 19.20 km2, a perimeter of 24.79 km, an elongated shape, low susceptibility to flooding, altitudes from 261 to 346 m, predominance of smooth wavy relief (47.45%), 90.36% from the area apt to extremely apt to agricultural mechanization and with low influence on the spread of fires, drainage network with a dendritic pattern, 5th drainage order, high density of springs, high drainage density, maintenance coefficient of 342.7 m2 m-1, wandering main channel and low concentration time. The Cutia river microbasin has the potential to implement agricultural systems, however, soil and water conservation management practices are recommended to mitigate the impact of these systems on natural resources. Studies on the spatial distribution of native vegetation in areas protected by law in the microbasin (legal reserves and permanent preservation areas) are also recommended, to assist in the delimitation of priority areas for the conservation of water resources.